AN AYURVEDIC PERSPECTIVE TO COGNITIVE BEHAVIOURAL THERAPY VIS A VIS SATWAVAJAYA CHIKITSA (International Journal of Ayurveda and Pharma Research, 2016)
Ayurveda, the science of life is regarded as the complete health care system for prevention as well as treatment of different diseases. It emphasizes on sustaining the equilibrium of body, mind and soul for the maintenance of proper health. Based on these three aspects Ayurveda suggested three treatment modalities i.e. Daivavyapashraya, Yuktivyapashraya and Satwavajaya Chikitsa. Satwavajaya is the comprehensive psychosomatic-spiritual approach to the preservation and treatment of both physical and mental health and is described as the major non-pharmacological approach to the treatment of different diseases. Though Psychotherapy is only a century old in western medicine, it is nothing new in Ayurveda, as the ancient system was well aware of psychic means of curing diseases. In fact, in the history of Ayurvedic medicine, Psychotherapy is as old as drug therapy. When the contemporary art of psychotherapy and the knowledge of ancient science of Ayurveda is integrated, it becomes a powerful combination. Cognitive behavioral therapy which is a part of psychotherapy is widely in practice in the present era. This paper is an attempt to highlight the practice of age old concept of mental and health termed as Satwavajaya chikitsa and its current practice in the contemporary science as Cognitive Behavioral Therapy for the management of psychic disorders.